Quantitative pupillometry in comatose out‐of‐hospital cardiac arrest patients: A post‐hoc analysis of the TTH48 trial. Issue 7 (29th May 2022) - Paramanathan, Sansuthan; Grejs, Anders Morten; Søreide, Eldar; Duez, Christophe Henri Valdemar; Jeppesen, Anni Nørgaard; Reinertsen, Åse Johanne; Strand, Kristian; Kirkegaard, Hans
Abstract: Background: Quantitative pupillometry is an objective method to examine pupil reaction and subsequently grade the response on a neurological pupil index (NPi) scale from 0 to 5. The aim of the present sub‐study was to explore the long‐term prognostic value of NPi in comatose out‐of‐hospital cardiac arrest patients undergoing targeted temperature management (TTM). Methods: This planned sub‐study of the "Targeted temperature management for 48 versus 24 h and neurological outcome after out‐of‐hospital cardiac arrest: A randomized clinical trial." NPi was assessed from admission and throughout day 3 and linked to the Cerebral Performance Categories score at 6 months. We compared the prognostic performance of NPi in 65 patients randomized to a target temperature of 33 ± 1°C for 24 or 48 h. Results: The NPi values were not different between TTM groups ( p > .05). When data were pooled, NPi was strongly associated with neurological outcome at day 1 with a mean NPi of 3.6 (95% CI 3.4–3.8) versus NPi 3.9 (3.6–4.1) in the poor versus good outcome group, respectively ( p < .01). At day 2, NPi values were 3.6 (3.1–4.0) and 4.1 (3.9–4.2) ( p = .01) and at day 3, the values were 3.3 (2.6–4.0) and 4.3 (4.1–4.6), respectively ( p < .01). The prognostic ability of NPi, defined by area under the receiver operating characteristic curve was best at day three. Conclusion: Quantitative pupillometry measured by NPi was not different in the two TTM groups, but overall, significantly associated with good and poor neurological outcomes at 6 months. NPI has a promising diagnostic accuracy, but larger studies are warranted.